Development of nanoformulation of picroliv isolated from Picrorrhiza kurroa. Issue 3 (1st June 2016) - Guliani, Anika; Kumari, Avnesh; Kumar, Dharmesh; Yadav, Sudesh Kumar
Abstract : Picroliv, a mixture of picroside I and kutkoside isolated from rhizome of Picrorrhiza kurroa has been reported for many pharmaceutical properties such as hepatoprotective, anticholestatic, antioxidant and immune‐modulating activity. However, picroliv possessed lesser efficacy due to its poor aqueous solubility and lesser bioavailability. To find solution, picroliv was loaded into biodegradable poly lactic acid nanoparticles (PLA NPs) using solvent evaporation method. The picroliv‐loaded PLA NPs were characterised by UV–vis spectroscopy, atomic force microscopy, transmission electron microscopy, Fourier transform infrared and Zeta sizer. The size of picroliv‐loaded PLA NPs was 182 ± 20 nm. Zeta potential of picroliv‐loaded PLA NPs was −23.5 mV, indicated their good stability. In vitro picroliv release from picroliv‐loaded PLA NPs showed an initial burst release followed by slow and sustained release. The efficacy of picroliv‐loaded PLA NPs was assessed against KB cell lines. Blank PLA NPs showed no cytotoxicity on KB cells. The picroliv‐loaded PLA NPs showed more cytotoxic activity on KB cells as compared to the pure drug. Hence, the developed picroliv nanoformulation would find potential application in pharma‐sector.